2019
DOI: 10.1177/1464884919872076
|View full text |Cite
|
Sign up to set email alerts
|

Burning out and turning off: Journalists’ disconnection strategies on social media

Abstract: This study explores forms of social media fatigue described by professional journalists, including frustration with the perception of their increased affective labor, dissatisfaction with communication environments on particular social media platforms, and increased anxiety about the possible impact of social media use on both their professional reputations and personal well-being. We argue that these forms of social media fatigue have influenced new professional practices on social media practice that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In certain situations, especially outside the workplace, refraining from ATB communication helped journalists to find a balance between work and life. Journalistic work has characteristics that easily blur the boundaries between different domains of life (Bossio & Holton, 2019;Robinson, 2011;Snyder et al, 2019). In order to find a balance, journalists set boundaries explicitly, for example, by saying 'I don't want to hear about possible mistakes in a news story before I'm at work'.…”
Section: Discussionmentioning
confidence: 99%
“…In certain situations, especially outside the workplace, refraining from ATB communication helped journalists to find a balance between work and life. Journalistic work has characteristics that easily blur the boundaries between different domains of life (Bossio & Holton, 2019;Robinson, 2011;Snyder et al, 2019). In order to find a balance, journalists set boundaries explicitly, for example, by saying 'I don't want to hear about possible mistakes in a news story before I'm at work'.…”
Section: Discussionmentioning
confidence: 99%
“…This is noteworthy, as previous research suggested that men journalists are ascribed higher social capital and engaging with them could strengthen women's social capital (Prandner 2013). In general, women journalists' tweeting behaviour could be explained with the risk of being exposed to hostility and harassment associated with increased visibility in the network (Lewis and Molyneux 2018), or with a strategic professional use of social media through disconnection (Bossio and Holton 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Platforms have for the most part been unwilling to pay for the news they host, have not returned significant revenues to the news media via referred traffic or advertising deals, and have changed content curation algorithms without warning, reducing traffic to news websites, as occurred with Facebook in 2017 and 2018 (Flew 2019). Social media news sharing has also radically re-shaped how journalism is selected, distributed, discussed, and valued, with reporters often conflicted about the attention given to social media metrics and the demands of social media interaction (Bossio and Holton 2019). Even as there is "a rapid and ongoing merging in the functions of publishers and platforms, and an often surprisingly high level of involvement from platform companies in influencing news production" (Tow Center 2018, 3), socially shared disinformation is also contributing to a decline in trust in journalism (Park et al 2020).…”
Section: Deteriorating Platform-publisher Relationshipmentioning
confidence: 99%